A practicable strategy for enrichment and separation of four minor flavonoids including two isomers from barley seedlings by macroporous resin column chromatography, medium‐pressure LC, and high‐speed countercurrent chromatography. Issue 9 (13th March 2019) - Wang, Nana; Chen, Tao; Yang, Xue; Shen, Cheng; Li, Hongmei; Wang, Shuo; Zhao, Jingyang; Chen, Jilin; Chen, Zhi; Li, Yulin
Abstract: Separation of minor compounds especially with similar polarities and structures from complex samples is a challenging work. In the present study, an efficient method was successfully established by macroporous resin column chromatography, medium‐pressure liquid chromatography, and high‐speed countercurrent chromatography for separation of four minor flavonoids from barley seedlings. Macroporous resin column chromatography and medium‐pressure liquid chromatography were used for enrichment of these four flavonoids. High‐pressure liquid chromatography analysis showed the total content of these four flavonoids increased from 2.2% in the crude extract to 95.3% in the medium‐pressure liquid chromatography fraction. It was indicated that the combination of macroporous resin column chromatography and medium‐pressure liquid chromatography could be a practicable strategy for enrichment of minor compounds from complex sample. Then, high‐speed countercurrent chromatography was employed for separation of these four flavonoids using ethyl acetate/ n ‐butanol/water (0.1% glacial acetic acid) (4:1:5, v/v/v) as solvent system. As a result, four flavonoids including two isomers with purities higher than 98% were obtained. Interestingly, two flavonoids existing in one high‐pressure liquid chromatography peak were also successfully separated. All these indicated high‐speed countercurrent chromatography had great potential for separation of compounds with similar structures and polarities. This study provides a reference for efficient enrichment and separation of minor compounds from complex sample.